Detection of Red Dye in Diesel Oil - B Varughese; H Khawaja (International Journal of Multiphysics, 2017)
Developing a sensitive and effective instrument for detecting the presence of red dye in diesel fuel is very advantageous for governments in preventing tax loss by controlling illegal use of the diesel fuel.